2022
DOI: 10.1155/2022/8799429
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Concrete Compressive Strength Based on the BP Neural Network Optimized by Random Forest and ISSA

Abstract: In modern engineering construction, the compressive strength of concrete determines the safety of engineering structure. BP neural network (BPNN) tends to converge to different local minimum points, and the prediction accuracy is not high in the prediction of the compressive strength of concrete. Therefore, a prediction model based on the BPNN optimized by improved sparrow search algorithm (ISSA) and random forest (RF) is proposed to enhance the generalization ability and prediction accuracy of BPNN for compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It was found that the optimal neural network structure selected by the ABC method consists of two layers, and the developed model (CFNN-ABC) can accurately predict the compressive strength of UHPFRC. Other similar studies [20][21][22][23][24][25][26] reported the successful application of a BP neural network, probabilistic neural network, and a depth neural network in the early age strength prediction of high-strength concrete. In general, most of the first types of methods are ANN-based prediction methods.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that the optimal neural network structure selected by the ABC method consists of two layers, and the developed model (CFNN-ABC) can accurately predict the compressive strength of UHPFRC. Other similar studies [20][21][22][23][24][25][26] reported the successful application of a BP neural network, probabilistic neural network, and a depth neural network in the early age strength prediction of high-strength concrete. In general, most of the first types of methods are ANN-based prediction methods.…”
Section: Introductionmentioning
confidence: 98%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%